2014
DOI: 10.1186/1471-2458-14-282
|View full text |Cite
|
Sign up to set email alerts
|

Child sexual abuse in religiously affiliated and secular institutions: a retrospective descriptive analysis of data provided by victims in a government-sponsored reappraisal program in Germany

Abstract: BackgroundThe disclosure of widespread sexual abuse committed by professional educators and clergymen in institutions in Germany ignited a national political debate, in which special attention was paid to church-run institutions. We wanted to find out whether the nature of the abuse and its effect on victims differed depending on whether the abuse had been experienced in religiously affiliated versus secular institutions.MethodsIn 2010, the German government established a hotline that victims could contact ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 25 publications
2
42
0
5
Order By: Relevance
“…It was found that CSA-W usually differed from child sexual abusers not working with children (CSA) in so far as they were older, better educated, and less likely to be in an adult relationship, while they did not differ concerning the frequency of having experienced sexual abuse themselves (Colton, Roberts, & Vanstone, 2010;Sullivan & Beech, 2004;Turner et al, 2014a). Recently, Turner and colleagues (2014a) reported that CSA-W were more likely to show indicators for pedophilic sexual interests while at the same time they showed fewer indicators for antisocial behaviors and reported fewer previous problems with alcohol compared to CSA not working with children (Turner et al, 2014a; see also Langevin, Curnoe, & Bain, 2000;Parkinson, Oates, & Jayakody, 2012;Spröber et al, 2014;Sullivan, Beech, Craig, & Gannon, 2011 for similar findings). Due to this constellation of risk factors it was concluded that CSA-W seem to exhibit more specific risk factors for sexual reoffending while they are not so much in danger for general or violent reoffending (Turner et al, 2014b).…”
Section: Characteristics and Risk Factors Of Child Sexual Abusers Wormentioning
confidence: 98%
See 1 more Smart Citation
“…It was found that CSA-W usually differed from child sexual abusers not working with children (CSA) in so far as they were older, better educated, and less likely to be in an adult relationship, while they did not differ concerning the frequency of having experienced sexual abuse themselves (Colton, Roberts, & Vanstone, 2010;Sullivan & Beech, 2004;Turner et al, 2014a). Recently, Turner and colleagues (2014a) reported that CSA-W were more likely to show indicators for pedophilic sexual interests while at the same time they showed fewer indicators for antisocial behaviors and reported fewer previous problems with alcohol compared to CSA not working with children (Turner et al, 2014a; see also Langevin, Curnoe, & Bain, 2000;Parkinson, Oates, & Jayakody, 2012;Spröber et al, 2014;Sullivan, Beech, Craig, & Gannon, 2011 for similar findings). Due to this constellation of risk factors it was concluded that CSA-W seem to exhibit more specific risk factors for sexual reoffending while they are not so much in danger for general or violent reoffending (Turner et al, 2014b).…”
Section: Characteristics and Risk Factors Of Child Sexual Abusers Wormentioning
confidence: 98%
“…Holt & Massey, 2013;Spröber et al, 2014;Sullivan & Beech, 2004;Turner, Rettenberger, Lohmann, Eher, & Briken, 2014a). It was found that CSA-W usually differed from child sexual abusers not working with children (CSA) in so far as they were older, better educated, and less likely to be in an adult relationship, while they did not differ concerning the frequency of having experienced sexual abuse themselves (Colton, Roberts, & Vanstone, 2010;Sullivan & Beech, 2004;Turner et al, 2014a).…”
Section: Characteristics and Risk Factors Of Child Sexual Abusers Wormentioning
confidence: 99%
“…In May 2010, again in response to an increased public awareness of the sexual abuse of children, the German government set up a confidential telephone line for victims to report such abuse. In the first 18 months, 4208 people contacted the service to report being sexually abused as children, 534 of whom had been abused in Catholic or Protestant institutions (Spröber et al, ).…”
Section: The Scale Of Sexual Abuse Within Religious Settingsmentioning
confidence: 99%
“…Einleitung Die in den letzten Jahren von der Presse aufgegriffenen Fälle von schwerster Kindesmisshandlung und -vernachlässigung mit Todesfolge sowie Fälle von sexueller Misshandlung in großem Ausmaß (katholische Kirche, Reformpädagogik) haben zu einer entsprechenden Sensibilisierung der Öffentlichkeit geführt [1]. Auch wenn es sich bei den verschiedenen Formen der Kindesmisshandlung und -vernachlässigung nicht um eigene Krankheitsentitäten im eigentlichen Sinne handelt, ist dennoch neben den unmittelbaren körperlichen Verletzungsfolgen und den Folgen der Mangelversorgung mit einer Reihe von langfristigen psychischen Störungen zu rechnen, die sich nachhaltig negativ auf individuelle Lebensläufe auswirken.…”
Section: Kindesmisshandlung Aus Pädiatrischer Sichtunclassified